PERANAN TRANSPORTASI LAUT DALAM MENUNJANG ARUS BARANG DAN ORANG DI KECAMATAN MALIGANO KABUPATEN MUNA - Jusna, Jusna; Nempung, Tibertius (JURNAL EKONOMI UHO, 2016)
This study aimed to determine the roles of sea transportation in supporting the flow of goods and people at Maligano District in Muna Regency. Sources of information used in this study were 7 informants, comprising of: 1 head of Maligano District (key informant), 2 merchants, 2 farmers, and 2 ship owners. Data were analyzed using a method of descriptive analysis by describing the characteristics and condition of the subject of the study or by analyzing the data obtained descriptively. Results of analyzing the obtained data led the researcher to conclude that the construction of port and procurement of K.M. Rembulan and speed boats had played a role in the increase of merchants or people doing economic activities around the port, resulting in the increase of people’s incomes, as well as in the flow of goods and people as can be seen from the increased number of passengers and quantity and kinds of goods that are transported via Maligano-Raha route since it is easier now for the people to move between the two areas by sea